Flexible freight bag with self-cleaning function and manufacturing method thereof
By adding nano-scale titanium dioxide powder and waterproof film to the braided layer of the container bag, and spraying Silane-Siloxane composite coating and fluorinated polymer on the outer surface, the shortcomings of the container bag in terms of cleaning and hygiene are solved, and the self-improvement of the container bag is achieved. Clean, waterproof and weather-resistant effects.
Patent Information
- Application Number
- CN202411952955.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing container bags have shortcomings in terms of cleaning and hygiene, making them difficult to remove stains and harmful substances, and are prone to absorb water and become moisture in humid environments, and are not weather-resistant and chemical corrosion-resistant.
Nano-scale titanium dioxide powder is woven into a cloth with polyethylene or polypropylene fibers, combined with a waterproof film and Silane-Siloxane composite coating to form a container bag with self-cleaning function and hydrophobic properties.
It realizes the self-cleaning function of container bags, significantly reduces stain adhesion, improves waterproof performance and weather resistance, and enhances chemical corrosion resistance and service life.
Smart Images

Figure CN119460451A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of container bags, in particular to a container bag with a self-cleaning function and a manufacturing method thereof. Background Art
[0002] In the field of logistics, warehousing and transportation, container bags, as an important packaging material, are widely used in the loading and transportation of various items;
[0003] However, existing container bags have shortcomings in terms of cleaning and hygiene. Since container bags are easily exposed to various stains and harmful substances during use, these stains and substances are often difficult to remove, which not only affects the appearance of the container bags, but also may cause pollution to the loaded items. In addition, the stains on the surface of the container bags may also become a breeding ground for microorganisms, posing a threat to the hygiene and safety of the items.
[0004] In addition, in a humid environment or when encountering rainy weather, the container bag easily absorbs water and becomes damp, causing the items inside to become damp and deteriorate. This not only affects the quality of the items, but may also cause economic losses. At the same time, the existing container bags also have certain limitations in terms of strength and wear resistance. With the development of the logistics industry, higher requirements are placed on the load and friction bearing capacity of the container bags.
[0005] Existing container bags also have shortcomings in terms of weather resistance and chemical corrosion resistance. In harsh climatic conditions and chemical environments, the performance of container bags is easily affected, and problems such as aging and deformation occur. This not only affects the use of container bags, but may also cause damage to the loaded items.
[0006] To this end, technical personnel in this field have proposed a self-cleaning container bag and a manufacturing method thereof, aiming to manufacture a container bag having excellent waterproof properties and self-cleaning ability, as well as high strength and wear resistance, good weather resistance and chemical corrosion resistance, so as to achieve high efficiency and sustainability of the container bag in various application scenarios. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a container bag with a self-cleaning function and a manufacturing method thereof to solve the problems raised in the background technology.
[0008] According to a first aspect of the present disclosure, a container bag with a self-cleaning function is proposed, comprising a bag body, a waterproof membrane installed in the bag body, a woven layer provided inside the bag body, a coating layer and a hydrophobic layer provided on the outer surface of the bag body, nano-scale titanium dioxide is added to the woven layer, a fluorinated polymer is added to the hydrophobic layer, and a Silane-Siloxane composite coating is added to the coating layer.
[0009] According to a second aspect of the present disclosure, a method for manufacturing a container bag with a self-cleaning function is proposed, which is applied in the first aspect and comprises the following steps:
[0010] S1. Evenly mixing nano-sized titanium dioxide powder into polyethylene or polypropylene fibers, weaving the fibers into cloth by melt spinning technology to form a woven layer;
[0011] S2, cutting the waterproof membrane into a shape and size matching the braided layer, and fixing it on the inside of the braided layer;
[0012] S3. Use heat sealing and sewing technology to form the structure of the entire container bag and make all interfaces tight;
[0013] S4. Evenly apply the Silane-Siloxane composite coating on the outer surface of the woven layer of the container bag to form a coating layer;
[0014] S5. After the coating layer is dried and solidified, spraying the fluorinated polymer solution evenly on the surface of the coating layer to form a hydrophobic layer;
[0015] S6. Send the finished container bags into the oven for drying and curing. After inspection and testing, the production is completed.
[0016] Preferably, in step S1, nano-scale titanium dioxide powder with high purity and uniform particles is used as an additive, polyethylene or polypropylene fiber is used as a substrate, and the nano-scale titanium dioxide powder is mixed with polyethylene or polypropylene fiber, the amount of nano-scale titanium dioxide added is 1%-5% of the weight ratio of the polymer, and the mixing time is 5-15 minutes;
[0017] The mixed fiber raw materials are fed into the melting chamber of the melt spinning machine and heated to a molten state at a temperature of 160-230°C to melt them into a melt;
[0018] In the molten state, the molten fibers are extruded through a spinning nozzle to form continuous fiber filaments, and the final fiber diameter is between 0.1-0.5mm;
[0019] After the fibers are cooled in air or water, they are further processed by stretching equipment to form the woven layer and the woven fabric is heat-set.
[0020] Preferably, the waterproof membrane material used in step S2 is polyurethane or polyvinyl fluoride. When cutting the waterproof membrane, a margin of 1-2 cm is reserved as an overlapping edge according to the size of the braided layer, so that the waterproof membrane can completely cover the inner surface of the braided layer;
[0021] Before fixing the waterproof membrane, pre-treat the inside of the woven layer, including cleaning and dust removal;
[0022] Place the cut waterproof membrane flatly on the inside of the woven layer so that it fits perfectly with the woven layer without any gaps, and use hot pressing, sewing, and pasting to fix the waterproof membrane on the inside of the woven layer.
[0023] Preferably, in step S4, before the coating operation, the outer surface of the braided layer is cleaned, including removing grease and dust, and making the surface of the braided layer dry and free of moisture;
[0024] Pour the Silane-Siloxane composite coating material into a container and stir it thoroughly with a stirrer to make the coating material uniform and free of precipitation;
[0025] Use a sprayer or spray gun to evenly spray the mixed Silane-Siloxane on the outer surface of the braided layer at a spraying distance of 20-30cm and a coating thickness of 10-50μm;
[0026] Place the coated bulk bag in a drying room or a well-ventilated place for drying and curing. The drying temperature is 25-60℃ and the drying time is 0.5-1.5h.
[0027] Preferably, the fluorinated polymer used in step S5 is polytetrafluoroethylene or fluorinated siloxane, which is diluted with deionized water before use;
[0028] When the coating is completely dry and cured, pre-treat the coating, including light sanding or dusting;
[0029] Use a spraying device to evenly spray the fluorinated polymer solution on the surface of the coating layer. During the spraying process, keep the distance between the spraying device and the surface of the coating layer at 20-30 cm, and use horizontal / vertical alternating spraying;
[0030] Use two spraying methods, the thickness after the first spraying is 15μm, and place it in a well-ventilated place, and the drying time is 1h; after it dries, spray it for the second time, the thickness increases by 5μm after spraying, the drying time is 1h, and the final hydrophobic layer thickness is 20μm;
[0031] During the spraying process, microstructures are created on the surface of the bag, including nanoparticles and micron-sized pits.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention adds nano-scale titanium dioxide powder to the woven layer, so that the container bag has a self-cleaning function and a photocatalytic degradation ability, thereby significantly reducing the adhesion of stains and reducing the difficulty of cleaning. At the same time, it is helpful to decompose and remove harmful substances on the surface to keep the container bag clean and hygienic; and by fixing a waterproof film on the inner side of the woven layer and spraying a fluorinated polymer solution on the surface of the coating layer to form a hydrophobic layer, the container bag has excellent waterproof performance, thereby effectively preventing moisture from penetrating into the interior of the container bag and protecting the loaded items from moisture.
[0034] 2. The present invention uses polyethylene or polypropylene fiber as the base material and combines it with melt spinning technology to weave a woven layer with high strength, wear resistance, tear resistance and other properties, so that the container bag can withstand greater loads and friction during use, thereby extending its service life.
[0035] 3. The present invention not only improves the weather resistance of the container bag by coating the Silane-Siloxane composite coating, but also enhances its chemical corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention is a flow chart of a method for manufacturing a container bag with a self-cleaning function. DETAILED DESCRIPTION
[0037] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0038] Embodiment 1: The present invention provides a container bag with a self-cleaning function, comprising a bag body, a waterproof membrane installed in the bag body, a woven layer provided in the bag body, a coating layer and a hydrophobic layer provided in the inner surface of the bag body, nano-scale titanium dioxide added to the woven layer, a fluorinated polymer added to the hydrophobic layer, and a Silane-Siloxane composite coating added to the coating layer.
[0039] As can be seen from the above, nano-scale titanium dioxide (TiO2) can generate free radicals under ultraviolet light, decompose surface dirt and organic matter, and achieve a self-cleaning effect; combined with fluorinated polymers, a hydrophobic layer is formed, making it easy for liquids or dirt to roll off. Anti-fouling coating is applied to the outer surface, and Silane-Siloxane composite coating is used to form a protective film that can decompose dirt, which effectively plays a photocatalytic role in combination with TiO2.
[0040] Embodiment 2: The present invention also provides a method for manufacturing a container bag with a self-cleaning function, which is applied in Embodiment 1 and comprises the following steps:
[0041] S1. Evenly mixing nano-sized titanium dioxide powder into polyethylene or polypropylene fibers, weaving the fibers into cloth by melt spinning technology to form a woven layer;
[0042] Nano-scale titanium dioxide powder with high purity and uniform particles is used as an additive to improve the self-cleaning performance and photocatalytic degradation ability of the braided layer, and polyethylene or polypropylene fiber is used as a substrate. The nano-scale titanium dioxide powder is mixed with the polyethylene or polypropylene fiber. During mixing, mechanical stirring, ultrasonic dispersion and other methods are used to ensure that the nano-scale titanium dioxide powder is evenly distributed in the fiber. The addition amount of nano-scale titanium dioxide is 1%-5% of the weight ratio of the polymer, and the mixing time is 5-15 minutes;
[0043] The mixed fiber raw materials are fed into the melting chamber of the melt spinning machine and heated to a molten state at a temperature of 160-230°C to melt them into a melt;
[0044] In the molten state, the molten fibers are extruded through a spinning nozzle to form continuous fiber filaments, and the final fiber diameter is between 0.1-0.5mm;
[0045] After the fiber is cooled in air or water, it is further processed by stretching equipment to form a braided layer, and the braided cloth is heat-set to eliminate internal stress and deformation during the braiding process and improve the dimensional stability and heat resistance of the braided layer. Nano-scale titanium dioxide powder is evenly mixed into polyethylene or polypropylene fibers and woven into cloth through melt spinning technology to form a braided layer with self-cleaning function. This braided layer not only has high strength, wear resistance, tear resistance and other properties, but also has excellent self-cleaning performance and photocatalytic degradation ability.
[0046] S2, cutting the waterproof membrane into a shape and size matching the braided layer, and fixing it on the inside of the braided layer;
[0047] The waterproof membrane material used is polyurethane or polyvinyl fluoride. When cutting the waterproof membrane, a margin of 1-2 cm is reserved as an overlapping edge according to the size of the woven layer so that the waterproof membrane can completely cover the inner surface of the woven layer;
[0048] Before fixing the waterproof membrane, pre-treat the inner side of the braided layer, including cleaning and dust removal, to ensure that the waterproof membrane can be firmly attached to the braided layer. At the same time, a layer of special adhesive or glue can be applied to the inner side of the braided layer to enhance the adhesion between the waterproof membrane and the braided layer.
[0049] Place the cut waterproof membrane flatly on the inside of the woven layer so that it fits the woven layer completely without any gaps, and fix the waterproof membrane on the inside of the woven layer using hot pressing, sewing, and pasting. When sewing, make sure that the stitches are tight and even, and will not damage the integrity of the waterproof membrane; when pasting, make sure that the adhesive or glue is evenly applied and will not penetrate the outside of the woven layer. After the fixation is completed, conduct a comprehensive inspection of the container bag to ensure that there are no bubbles or gaps between the waterproof membrane and the woven layer, and that it is firmly fixed.
[0050] When using adhesive, apply a proper amount of glue to the inside of the braided layer, ensuring that it is evenly distributed and not too thick; carefully align the cut waterproof membrane to the inside of the braided layer to avoid bubbles or wrinkles; gently press from the center outward to ensure that the membrane fits firmly on the braided layer. Then leave it for a certain period of time to ensure that the glue is fully cured, or put it in an oven to accelerate the curing.
[0051] S3. Use heat sealing and sewing technology to form the structure of the entire container bag and make all interfaces tight;
[0052] S4. Evenly apply the Silane-Siloxane composite coating on the outer surface of the woven layer of the container bag to form a coating layer;
[0053] Before coating, clean the outer surface of the braided layer, including removing grease and dust, and make the surface of the braided layer dry and free of moisture;
[0054] Pour the Silane-Siloxane composite coating material into a container and stir it thoroughly with a stirrer to make the coating material uniform and free of precipitation;
[0055] Use a sprayer or spray gun to evenly spray the mixed Silane-Siloxane on the outer surface of the braided layer at a spraying distance of 20-30cm and a coating thickness of 10-50μm;
[0056] Place the coated bulk bag in a drying room or a well-ventilated place for drying and curing. The drying temperature is 25-60℃ and the drying time is 0.5-1.5h.
[0057] The Silane-Siloxane composite coating is evenly coated on the outer surface of the woven layer of the container bag to form a coating layer with excellent performance. This coating layer can not only improve the weather resistance, chemical corrosion resistance and self-cleaning performance of the container bag, but also enhance the strength and wear resistance of the woven layer, thereby extending the service life of the container bag.
[0058] S5. After the coating layer is dried and solidified, spraying the fluorinated polymer solution evenly on the surface of the coating layer to form a hydrophobic layer;
[0059] The fluorinated polymer used is polytetrafluoroethylene or fluorinated siloxane, which is diluted with deionized water before use; before use, the fluorinated polymer solution is stirred evenly without precipitation or stratification.
[0060] When the coating is completely dry and cured, pre-treat the coating, including light sanding or dusting, to improve the adhesion between the fluorinated polymer solution and the coating;
[0061] Use a spraying device to evenly spray the fluorinated polymer solution on the surface of the coating layer. During the spraying process, use a uniform sweeping motion to avoid repeated spraying at the same location resulting in uneven thickness. Keep the distance between the spraying device and the surface of the coating layer at 20-30cm, and use horizontal / vertical alternating spraying;
[0062] The spraying method is adopted twice. After the first spraying, the thickness is 15 μm. It is placed in a well-ventilated place and dried for 1 hour. After it is dried, the second spraying is carried out. The thickness increases by 5 μm after spraying. The drying time is 1 hour. The final hydrophobic layer thickness is 20 μm, forming a hydrophobic layer.
[0063] During the spraying process, microstructures, including nanoparticles and micron-sized pits, are created on the surface of the bag to simulate the "lotus leaf effect" to enhance hydrophobicity, making it easier for water droplets to roll and carry away attached dirt.
[0064] After the coating layer is dried and solidified, the fluorinated polymer solution is evenly sprayed on the surface of the coating layer to form a hydrophobic layer with excellent hydrophobic properties. This hydrophobic layer can not only improve the waterproof performance of the container bag, but also reduce the adhesion of stains and the difficulty of cleaning, thereby extending the service life of the container bag and reducing maintenance costs.
[0065] S6. Send the finished container bags into the oven for drying and curing. After inspection and testing, the production is completed.
[0066] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible without substantially departing from the novel teachings and advantages of the subject matter described in the application. Without departing from the scope of the present invention, other replacements, modifications, changes and omissions may be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the present invention is not limited to a specific embodiment, but extends to a variety of modifications still falling within the scope of the appended claims.
[0067] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.
[0068] It should be understood that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but for those of ordinary skill having the benefit of this disclosure, without undue experimentation, the development effort will be a routine task of design, fabrication, and production.
[0069] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A container bag with a self-cleaning function, characterized in that: The invention comprises a bag body, wherein a waterproof film is installed in the bag body, a woven layer is arranged inside the bag body, a coating layer and a hydrophobic layer are arranged on the outer surface of the bag body, nano-scale titanium dioxide is added to the woven layer, a fluorinated polymer is added to the hydrophobic layer, and a Silane-Siloxane composite coating is added to the coating layer.
2. A method for manufacturing a self-cleaning container bag, applied to a self-cleaning container bag as claimed in claim 1, characterized in that: The following steps are involved: S1. Evenly mixing nano-sized titanium dioxide powder into polyethylene or polypropylene fibers, weaving the fibers into cloth by melt spinning technology to form a woven layer; S2, cutting the waterproof membrane into a shape and size matching the braided layer, and fixing it on the inside of the braided layer; S3. Use heat sealing and sewing technology to form the structure of the entire container bag and make all interfaces tight; S4. Evenly apply the Silane-Siloxane composite coating on the outer surface of the woven layer of the container bag to form a coating layer; S5. After the coating layer is dried and solidified, spraying the fluorinated polymer solution evenly on the surface of the coating layer to form a hydrophobic layer; S6. Send the finished container bags into the oven for drying and curing. After inspection and testing, the production is completed.
3. The method for manufacturing a container bag with a self-cleaning function as claimed in claim 2, characterized in that: In step S1, high-purity, uniform-particle nano-scale titanium dioxide powder is used as an additive, polyethylene or polypropylene fiber is used as a substrate, and the nano-scale titanium dioxide powder is mixed with the polyethylene or polypropylene fiber, the amount of nano-scale titanium dioxide added is 1%-5% of the weight ratio of the polymer, and the mixing time is 5-15 minutes; The mixed fiber raw materials are fed into the melting chamber of the melt spinning machine and heated to a molten state at a temperature of 160-230°C to melt them into a melt; In the molten state, the molten fibers are extruded through a spinning nozzle to form continuous fiber filaments, and the final fiber diameter is between 0.1-0.5mm; After the fibers are cooled in air or water, they are further processed by stretching equipment to form the woven layer and the woven fabric is heat-set.
4. The method for manufacturing a container bag with a self-cleaning function as claimed in claim 2, characterized in that: The waterproof membrane material used in step S2 is polyurethane or polyvinyl fluoride. When cutting the waterproof membrane, a margin of 1-2 cm is reserved as an overlapping edge according to the size of the braided layer so that the waterproof membrane can completely cover the inner surface of the braided layer; Before fixing the waterproof membrane, pre-treat the inside of the woven layer, including cleaning and dust removal; Place the cut waterproof membrane flatly on the inside of the woven layer so that it fits perfectly with the woven layer without any gaps, and use hot pressing, sewing, and pasting to fix the waterproof membrane on the inside of the woven layer.
5. The method for manufacturing a container bag with a self-cleaning function as claimed in claim 2, characterized in that: In step S4, before the coating operation, the outer surface of the braided layer is cleaned, including removing grease and dust, and making the surface of the braided layer dry and free of moisture; Pour the Silane-Siloxane composite coating material into a container and stir it thoroughly with a stirrer to make the coating material uniform and free of precipitation; Use a sprayer or spray gun to evenly spray the mixed Silane-Siloxane on the outer surface of the braided layer at a spraying distance of 20-30cm and a coating thickness of 10-50μm; Place the coated bulk bag in a drying room or a well-ventilated place for drying and curing. The drying temperature is 25-60℃ and the drying time is 0.5-1.5h.
6. The method for manufacturing a container bag with a self-cleaning function as claimed in claim 2, characterized in that: The fluorinated polymer used in step S5 is polytetrafluoroethylene or fluorinated siloxane, which is diluted with deionized water before use; When the coating is completely dry and cured, pre-treat the coating, including light sanding or dusting; Use a spraying device to evenly spray the fluorinated polymer solution on the surface of the coating layer. During the spraying process, keep the distance between the spraying device and the surface of the coating layer at 20-30 cm, and use horizontal / vertical alternating spraying; Use two spraying methods, the thickness after the first spraying is 15μm, and place it in a well-ventilated place, and the drying time is 1h; after it dries, spray it for the second time, the thickness increases by 5μm after spraying, the drying time is 1h, and the final hydrophobic layer thickness is 20μm; During the spraying process, microstructures are created on the surface of the bag, including nanoparticles and micron-sized pits.